2015
DOI: 10.3389/fmats.2015.00021
|View full text |Cite
|
Sign up to set email alerts
|

Porous Properties of Pillared Carbons Prepared from the Thermal Reduction of Graphite Oxide Repeatedly Silylated with Methyltrichlorosilanes

Abstract: Pillared carbons with interlayer spacings of 1.27-1.37 nm were obtained from graphite oxide repeatedly silylated with methyltrichlorosilane, when the content of it was higher than 1.5/GO unit. The BET surface area of the resulting pillared carbons reached 723 m 2 /g and decreased with the increase in the content of Si because of the increase in the density of pillar. Based on the intercalation behaviors of n-alkylamine molecules into pillared carbons, it has been concluded that the entrance for organic molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…Characterisation of the textural properties is also a routine analysis when synthesising new materials. In this sense, Matsuo et al (2015) characterised the porous texture of pillared carbons that had been prepared from the thermal reduction of graphite oxide. The samples were silylated with methyltrichlorosilane at various times in a study in which the effect of the content of Si on the porous properties of the pillared carbons was evaluated.…”
Section: Physical Surface Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterisation of the textural properties is also a routine analysis when synthesising new materials. In this sense, Matsuo et al (2015) characterised the porous texture of pillared carbons that had been prepared from the thermal reduction of graphite oxide. The samples were silylated with methyltrichlorosilane at various times in a study in which the effect of the content of Si on the porous properties of the pillared carbons was evaluated.…”
Section: Physical Surface Propertiesmentioning
confidence: 99%
“…Following the idea of a network, 3D carbon materials can be formed interestingly by pillaring carbon materials. Matsuo et al (2015) reported the synthesis of pillared carbons with different pillar densities from the thermal reduction of graphite silylated with methyltrichlorosilane. A further study by Matsuo and Araki (2017) reported the use of different silanes to obtain pillared carbon thin films with hydrophobic pillars that prevent the intercalation of smaller water molecules.…”
Section: D Carbon Materials Derived From Polymersmentioning
confidence: 99%
“…24,[28][29][30] Some intercalated GO materials (e.g., siloxane derivative) were also converted into pillared carbons using chemical reduction or thermal deoxygenation. [31][32][33][34][35][36] The experimental specific surface area (SSA) reported for some PGO materials (B400-1000 m 2 g À1 ) is significantly higher compared to pristine graphite oxide. However, in other cases, it is not clear if the expanded lattice is indeed porous (demonstrating a high surface area) or the expansion is related to intercalation rather than to pillaring.…”
Section: Introductionmentioning
confidence: 99%
“…Matsuo et al have shown that the BET surface area of porous graphene heterostructures can be increased up to 756 m 2 /g after insertion of two different organosilanes between graphene layers in a two-step process (Matsuo et al, 2012a ). The same group also showed that repeating silylation process of graphene oxide with trichlorosilane affects the density of the siliceous pillars, and allows to tailor the BET surface area between 77 and 723 m 2 /g (Matsuo et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%